SYNTHESIS OF RADIOPHARMACEUTICAL WITH RHENIUM-188 AND LIPIODOL - G. E. Kodina; A. O. Malysheva; N. A. Taratonenkova; E. A. Lyamtseva; N. A. Konstantinov (Разработка и регистрация лекарственных средств)
Radiopharmaceutical with rhenium-188 and lypiodol is synthesized in medical organizations from a kit of reagents and eluate from the 188W/188Re generator. The kit of reagents consists of three vials: lyophilized reagent N 1 containing tin dichloride, lyophilized reagent N 2 - sodium dithiobenzoate, and reagent N 3 - lipiodol. A domestic technology was developed for obtaining a lyophilized reagent containing tin dichloride. Quality control of the sodium perrhenate, 188Re solution obtained from the generator (eluate) should be carried out before each synthesis of the radiopharmaceutical. The results of quality control of radiopharmaceuticals synthesized from lyophilized reagent N 1 of domestic and imported production, showed their identity by index «radiochemical purity».